Recent advances in understanding and managing body dysmorphic disorder - David Mataix-Cols; Lorena Fernández de la Cruz; Georgina Krebs (BMJ Mental Health)
Body dysmorphic disorder (BDD) is a relatively common and disabling psychiatric disorder characterised by excessive and persistent preoccupation with perceived defects or flaws in one's appearance, which are unnoticeable to others, and associated repetitive behaviours (eg, mirror checking). The disorder generally starts in adolescence, but often goes unnoticed and is severely underdiagnosed. Left untreated, BDD typically persists and causes marked functional impairment in multiple domains. This clinical review considers recent advances in the epidemiology and classification of BDD, including its reclassification in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders under the new ‘Obsessive–Compulsive and Related Disorders’ chapter. Key issues in assessment are outlined including the use of validated screening instruments to minimise misdiagnosis and the importance of risk assessment in this population given the high rates of suicidality and inappropriate use of cosmetic treatments. In addition, current knowledge regarding the causes and mechanisms underlying BDD are summarised. The recommended treatments for BDD are outlined, namely cognitive behavioural therapy (CBT) and antidepressants, such as selective serotonin reuptake inhibitors. Both CBT and pharmacotherapy have been shown to be efficacious treatments for BDD in adult populations, and evidence is emerging to support their use in young people. Although the majority of patients improve with existing evidence-based treatment, a large proportion are left with clinically significant residual symptoms. Priorities for future research are therefore discussed including the need to further refine and evaluate existing interventions with the goal of improving treatment outcomes and to increase their availability.